Consensus in stem cell transplantation for pediatric solid tumors - Kuwahara, Cilmara; Franco, Simone; Milaré, Luiza; Castro Junior, Cláudio Galvão de; Seber, Adriana (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Solid tumors in the pediatric population are preferred treated in clinical national or international protocols, in which the work of pediatric oncology cooperative groups guides the therapeutic standards and advancements. The role of high-dose chemotherapy (HDC) and hematopoietic cell transplant (HCT) in the pediatric population is usually reserved for patients or subgroups of patients who have diseases with poor prognosis and sometimes are refractory to the best available treatment, in combination to conventional chemotherapy, surgical procedure, and radiation. The Pediatric Group of the Brazilian Society of Bone Marrow Transplantation and Cellular Therapy has revised its current consensus, providing updated recommendations for indications and conditioning protocols. This updated guidance emphasizes that, while HDC/HCT is an important tool for specific high-risk malignancies, several tumors continue to have no indication for autologous transplantation based on current evidence.